Rapid quantification of naive alloreactive T cells by TNF-α production and correlation with allograft rejection in mice - Brehm, Michael A. (American Society of Hematology, 2007)
Allograft transplantation requires chronic immunosuppression, but there is no effective strategy to evaluate the long-term maintenance of immunosuppression other than assessment of graft function. The ability to monitor naive alloreactive T cells would provide an alternative guide for drug therapy at early, preclinical stages of graft rejection and for evaluating tolerance-inducing protocols. To detect and quantify naive alloreactive T cells directly ex vivo, we used the unique ability of naive T cells to rapidly produce TNF-α but not IFN-γ. Naive alloreactive T cells were identified by the production of TNF-α after a 5-hour in vitro stimulation with alloantigen and were distinguished from effector/memory alloreactive T cells by the inability to produce IFN-γ. Moreover, naive alloreactive T cells were not detected in mice tolerized against specific alloantigens. The frequency of TNF-α–producing cells was predictive for rejection in an in vivo cytotoxicity assay and correlated with skin allograft rejection. Naive alloreactive T cells were also detected in humans, suggesting clinical relevance. We conclude that rapid production of TNF-α can be used to quantify naive alloreactive T cells, that it is abrogated after the induction of tolerance, and that it is a potential tool to predict allograft rejection.